2019
DOI: 10.1097/corr.0000000000000896
|View full text |Cite
|
Sign up to set email alerts
|

How are Electronic Health Records Associated with Provider Productivity and Billing in Orthopaedic Surgery?

Abstract: Background Electronic health records (EHRs) have become ubiquitous in orthopaedics. Although they offer certain benefits, they have been cited as a factor that can contribute to provider burnout. Little is known about the degree to which EHR adoption is associated with provider and practice characteristics or outpatient and surgical volume. Questions/purposes (1) What was the rate of EHR adoption in orthopaedics and how are physician and practice charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In contrast, for productivity and workload efficiency, the results of a survey indicated that physicians perceived that EHR adoption harmed productivity and increased their workload [ 28 , 34 , 45 ]. EHR implementation was reportedly associated with increased documentation effort and time, with little to no increase in clinical volume and little to no or perhaps a negative impact on clinical and surgical volume [ 38 , 39 , 41 ]. Increased documentation time because of EHR adoption resulted in a decrease in the time spent reviewing patient records and performing physical examinations [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, for productivity and workload efficiency, the results of a survey indicated that physicians perceived that EHR adoption harmed productivity and increased their workload [ 28 , 34 , 45 ]. EHR implementation was reportedly associated with increased documentation effort and time, with little to no increase in clinical volume and little to no or perhaps a negative impact on clinical and surgical volume [ 38 , 39 , 41 ]. Increased documentation time because of EHR adoption resulted in a decrease in the time spent reviewing patient records and performing physical examinations [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the reimbursement measure, EHR systems were thought to be responsible for significant improvements in the timeliness of clinical documentation and billing for reimbursement [ 30 , 41 , 76 ]. The analysis of Cheriff et al [ 37 ] documented that physicians who adopted EHRs in a large academic multispecialty physician group captured higher average monthly charges than before the use of EHRs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 studies examined productivity changes after EHR introduction, where productivity was mostly defined as average patient volumes. Of these studies, 3 revealed no statistically significant changes, hence neutral economic impacts [ 42 - 44 ]. Kaneko et al [ 45 ] showed a negative impact on multifactor productivity following EHR introduction in Japanese municipal hospitals.…”
Section: Resultsmentioning
confidence: 99%
“…Hospitals may be more likely to contract with practices that have hired care managers or with practices that have invested in health information technology systems, especially systems that are interoperable with the hospital's systems. By 2016, only about half of orthopedic providers had adopted electronic health records (Dandu et al, 2019). Orthopedic surgeon practices may merge to share in these high-cost investments.…”
Section: The Cjr Model and Provider Consolidationmentioning
confidence: 99%